The molecular basis of bacterial pathogenicity: an overview - Finlay, B. Brett (Henry Stewart Talks, 2009)
Overview of bacterial diseases and virulence factors, Toxins, Adherence mechanisms, Type III secretion systems, Intracellular survival mechanisms, Avoiding the immune system, Impact of microbiota, Antibiotics, Vaccines -Bioterrorism